Non-invasive vagus nerve stimulation: effects on trigeminal laser evoked potentials. Issue 1 (January 2019) - Ricci, K.; Vecchio, E.; Montemurro, A.; Spitzer, L.; Liebler, E.J.; de Tommaso, M.
Abstract : A portable transcutaneous non-invasive device that stimulates the cervical portion of the vagus nerve has been developed (GammaCore®) for the treatment of migraine. Cervical nVNS was shown to rapidly inhibit cortical spreading depression in rodents, providing important insights into the mode of action of nVNS. We aimed to test the effects of cervical nVNS on cortical responses and Gamma Band Oscillations (GBO) induced by painful laser stimuli delivered to the right and left forehead and hands in a cohort of twenty-eight migraine patients. Patients were selected and randomly assigned to active or sham nVNS stimulation on the neck bilaterally with GammaCore®. We recorded Laser evoked responses (LEPs) by stimulating bilaterally the hand and the forehead, in basal condition, during nVNS and sham stimulation and two minutes after stimulation. We observed a significant reduction of amplitude of the P2 wave from the forehead during active nVNS, as compared to basal and sham stimulation. However LEPs amplitude immediately recovered after stimulation session. The sham device induced an evident reduction of LEP amplitude, though not significant in respect to active device. Active nVNS seems to have a transitory effect on the transmission of trigeminal pain, which can contribute to induce changes of trigeminal function improving migraine.